(untitled) (Gestión y Gerencia, 2022)
This essay constitutes an advance of a historical investigation about the trajectory of this educational institution of Veterinary Medicine, the second created in the country, Universidad Centroccidental Lisandro Alvarado, and that almost completes the 6 decades of existence. A succinct tour that highlights events, facts, episodes and data, also showing evidence of its important contributions to comprehensive national development in the fields of animal health and sanitary care, public health and sustainable production.